“Respuesta del cultivo de brócoli (Brassica Oleracea Var. Itálica) a la aplicación de tres láminas de riego en las terrazas de banco en el campus Salache - UTC, 2023.” - Burbano Veintimilla, Marcos Ismael (2023)
Broccoli (Brassica oleracea var. Italica) is a native cool-season vegetable, with optimum temperatures for broccoli development considered to be between 10 and 20°C (50-68°F). They cannot tolerate drought; the quality of the final product will decrease significantly under water stress conditions. The present research has as its main objective to evaluate the "response of broccoli (brassica oleracea var. italica) crop to the application of three irrigation sheets in N-5 bench terraces in Salache campus, Latacunga canton, Cotopaxi province 2023". The treatments consisted of applying one sheet at 100% of crop evapotranspiration, and two deficit sheets at 90% and 80% of crop evapotranspiration (Etc), Once the research work was completed, it was concluded: The analysis of VARIANCE shows that there are significant differences in the application of three irrigation sheets. Treatment T3 (80% ETc) presented the greatest plant height (25.19 cm), number of leaves (18.13), leaf length (44.27 cm), and weight of the plant (0.19 kg) with respect to 100% ETc and 90% ETc. A lower water sheet (T3) gives a better response in broccoli crop development; as well as its yield. Evaluating water efficiency in broccoli cultivation in semiarid areas such as Salache, it is evident that T3 presented the best water use efficiency (4.43kg/m3), since a lower amount of water is required to produce almost twice the amount of T1 (2.61 kg/m3). under high-frequency localized irrigation in broccoli cultivation. The experimental design was a completely randomized block design with 3 replications. The results obtained allowed the identification of the phenological stages of broccoli. The analysis of variance and Tukey's test at 5% determined that there were no significant differences in the height, number of leaves, leaf length, and pellet weight at 30, 60, and 90 days of cultivation. In other words, the application of the three sheets does not influence the development of the broccoli crop until the day of harvest.